Issue of Valuation and Payment of Fees, Charges and Restitution Costs of the Forest Ecosystem Used for Road Projects - Januszewski, Damian; Łaguna, Teresa Maria; Osiecka, Agnieszka (Olsztyn Economic Journal, 2012)
This paper presents the issues related to the fees paid by entities for exclusion of a forest from production. Forests and forest lands are covered by statutory protection against change in use for purposes other than forest. The government has introduced fees and yearly charges for which the method of computation is included in the Act on Protection of Agricultural and Forest Lands (Act of 3 February 1995 on protection of agricultural and forest lands, Dz.U. of 2004 No. 121, item 1266). The total fees include a one-time fee, yearly charges and compensation for the early felling of standing timber if it has not reached felling age. The problem of valuation of the statutory fee, once-only fee, the year fees, compensation for early felling of standing timber and the problem of possible ecosystem restitution costs are all analysed in this work. The study also aimed at determining the amounts of fees and charges paid by a private entity for exclusion of 1 ha of forest land from production.A case study covering 1 ha of riparian forest excluded from production permanently was used as the method of study. The amounts of fees and charges due for exclusion of the forest from production and the costs of ecosystem restitution were computed. The study showed that the fees and charges imposed by the government do not satisfy the criterion of equivalency according to the principle that "the user pays" because of the omission of the costs of restoring the ecosystem.